ANALISIS USAHA BUDIDAYA JAMUR TIRAM PADA INDUSTRI “SUMBER URIP JAMUR” DI KOTA PALU SULAWESI TENGAH - Yamalia, Lesni; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2019)
This research was conducted in home industry of “Sumber Urip Jamur” in Palu City Central Sulawesi on April 2015. The aim of the research is to know the feasibility of oyster mushroom cultivation in “Sumber Urip Jamur” in Palu. The determination of respondent has done as purposive method. The number of respondents were 3 respondents, they are the head and the exchequer of “Sumber Urip Jamur”. Data of this research comprise of primary and secondary data. The data were analyzed using business feasibility analysis of ROI and JWPM. The result of this research showed that the income of oyster mushroom is Rp. 6.000.000 and the profit is Rp. 2.719.757 and ROI produced is 19%. The business capital will return after 2,74 year of 17 months because the production of oyster mushroom improved from 6 to 10 kg per day while the payback period is 2,74. Business of oyster mushroom is feasible cultivated with range of score of R/C of 1,82.